Analysis of the Effects of Palm Oil Fruit Extract (Elais Guineensis Jacq) with Histopathological Evaluation of the Liver Tissue of Male Wistar Rats (Rattus norvegicus) with Diabetes Mellitus After Streptozotocin Induction - Ilham Harahap, Azra Wifa; Medina Liza Lubis, Humairah (Jurnal Indonesia Sosial Sains, 2026)
Hyperglycemia is a chronic condition that can cause serious complications, such as liver damage and elevated SGOT and SGPT enzyme levels, which are closely related to Diabetes Mellitus (DM). Palm fruit (Elaeis guineensis Jacq.), which is rich in antioxidants such as carotenoids, vitamin E, flavonoids, alkaloids, saponins, and tannins, has antidiabetic and hepatoprotective potential. Streptozotocin selectively damages pancreatic β-cells, causing oxidative stress and decreased blood insulin levels. This research aims to analyze the effect of palm fruit extract (Elaeis guineensis Jacq.) by observing steatosis, inflammation, fibrosis, and necrosis. This study is a laboratory experimental study with a post-test–only control group randomized experimental design. There were five groups that received treatment for 28 days, namely KN (negative control, pellet feed), KP (positive control, streptozotocin), P1 (treatment 1, streptozotocin 30 mg/kg BW and palm fruit extract dose 100 mg/kg BW), P2 (treatment 2, streptozotocin 30 mg/kg BW and palm fruit extract dose 200 mg/kg BW), and P3 (treatment 3, streptozotocin 30 mg/kg BW and palm fruit extract dose 300 mg/kg BW). The results of this study were analyzed using the Kruskal–Wallis test and the Mann–Whitney test for comparisons between two independent groups. The Kruskal–Wallis test showed that the group comparison results obtained a value of p = 0.000. The Mann–Whitney test showed significant differences in the comparisons of KP with P1, P2, and P3 (p = 0.015 < 0.05; p = 0.007 < 0.05; p = 0.005 < 0.05). The dose of 300 mg/kg BW of palm fruit extract was the most optimal dose for improving the histopathological appearance of liver tissue in male Wistar rats (Rattus norvegicus).